Novel substrates for the automated and manual assay of endo-1, 4-β-xylanase. (5th June 2017) - Mangan, David; Cornaggia, Claudio; Liadova, Agnija; McCormack, Niall; Ivory, Ruth; McKie, Vincent A.; Ormerod, Aaron; McCleary, Barry V.
Abstract: endo -1, 4-β-Xylanase (EC 3.2.1.8) is employed across a broad range of industries including animal feed, brewing, baking, biofuels, detergents and pulp (paper). Despite its importance, a rapid, reliable, reproducible, automatable assay for this enzyme that is based on the use of a chemically defined substrate has not been described to date. Reported herein is a new enzyme coupled assay procedure, termed the XylX6 assay, that employs a novel substrate, namely 4, 6- O -(3-ketobutylidene)-4-nitrophenyl-β-4 5 - O -glucosyl-xylopentaoside. The development of the substrate and associated assay is discussed here and the relationship between the activity values obtained with the XylX6 assay versus traditional reducing sugar assays and its specificity and reproducibility were thoroughly investigated. Graphical abstract: Highlights: Chemoenzymatic synthesis of colourimetric substrates for endo -1, 4-β-xylanase. Development of an assay procedure (XylX6) employing the lead substrate. Assay of four GH10 and four GH11 endo -1, 4-β-xylanases using the XylX6 assay procedure. The repeatability/reproducibility of the assay is thoroughly investigated. The automation of this assay using a ChemWell ® -T system is demonstrated.